Entrepreneurship Development in the Balkans Perspective from Diverse Contexts - Ramadani, Veland (Lab for Entrepreneurship and Development Series, 2023)
Entrepreneurship Development in the Balkansdirectly engages questions of innovation and risk management within various types of entrepreneurship, including female, social, migrant, and corporate entrepreneurship in the context of the Balkans